Improving Student Learning Outcomes of Music Ensembles Using the Demonstration Method - Al Fajri, Sri Intan; Darma Putra , Irdhan Epria (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2024)
The purpose of this study was to improve the learning outcomes of music ensembles of grade X students using the sampling method. E 3 SMA Negeri 1 Palupuh. This type of research is classroom action research. The tools used are teaching aids, student observation sheets and tests. Data were collected through observation, interviews, tests and documentation. The data is analyzed using a percentage formula. The results proved that the exemplary method used by teachers can improve the appearance and learning outcomes of students when learning similar musical compositions, namely piano ensembles. The percentage of student learning activities in the first cycle was paying serious attention to the explanation from the teacher 55.5%, doing questions and answers 44.4%, doing teacher orders 48.1%, appearing in groups in front of the class 100%. After making improvements, the percentage of student learning activities increased, namely paying serious attention to explanations from the teacher 81.4%, doing questions and answers 70.3%, doing teacher orders 74%, appearing in groups in front of the class 100%. The use of sampling methods in class X. E 3 also affects student learning outcomes. This can be seen from the percentage of completeness of student learning outcomes in the first cycle, namely. 55.6%, which rose to 81.48% in the second cycle. With the sampling method, the average student learning outcomes in the first period were 68.9 and the second period rose to 85.6 with good score criteria.